#TITLE_ALTERNATIVE# - HADIANSYAH (NIM 12902002), FIKRI
Sea tides give an influence to the river flow that's connected with it. The river tides which is generated by this interaction between the sea and the river could be calculated analytically. This analytical calculation has an advantage which is its characteristic that's fit to general or universal condition. In this study, the analytical calculation using the Thabet's method of the river tides done in Berau River, East Borneo. This calculation was divided into elevation calculation and discharge calculation. Both results of this calculation were then compared with the data measured on the field. From the results of the calculations that's been done, show that the analytically calculated river water level variation was pretty good. Between the calculated and the measured water level variation, show a same phase with the difference in amplitude between 0,01 to 0,24 meter where the calculated water level variation amplitude is bigger than the measured amplitude with the tidal range vary between 1 to 2,8 meter . On the other hand, the calculation of the discharge variation hasn't show a good result.